Twister trouble - Schreiber, Ann; Speirs, John (New York Scholastic, 2000)
While on their way to Weatherama Amusement Park to attend the Wild Weather Show, Ms. Frizzle and her class get a first-hand lesson in the forces of nature as they fly directly into the heart of a powerful tornado
The Magic School Bus science chapter book ; v #5
Hurg
5
Keywords: Tornadoes -- Juvenile literature; Tornadoes